Theology And Civil Science According to Al-Farabi (Damascus University Journal of arts and humanities sciences, 2025)
This research reviews the most important political ideas included in Al-Farabi's main book in political philosophy: The Book of Opinions of the People of the Virtuous City and Its Opposites, with a focus on three problematic issues included in the book and linked to the philosophical system of The Second Master, the first of which is a methodology that focuses on the relationship of political science or civil science with theology, and the metaphysics of the total mind and the human self, and the second problem discusses the assumption that Al-Farabi has attached the sciences of theology and metaphysical issues to civil science in The Book of Opinions of the People of the Virtuous City, while the third problem is concerned withexamining the rational approach of Al-Farabi, in which he concluded the unity of the human mind, and then the equality of all individuals And human communities based on their shared.
Keywords: Civil Science; Theology; Global Citizen